First Report of AIDS-Related Burkitt’s Lymphoma Presenting as Bilateral Orbital Masses - Monica Alves de Almeida; Juliana Nesi Cardoso Migliano Porto; Ana Carolina de Brito Lyra; Luiz Arthur Calheiros Leite; Rodrigo Panno Basilio-de-Oliveira; Rogério Neves-Motta; Andréa Ramos Correa; Fernando Raphael de Almeida Ferry; Walter de Araujo Eyer-Silva; Ronaldo Grechi Pacheco (Case Reports in Infectious Diseases)
Burkitt’s lymphoma (BL) is an aggressive B-cell non-Hodgkin’s lymphoma and one of the fastest growing tumors in humans. It is an acquired immunodeficiency syndrome- (AIDS-) defining disease and occurs with relatively preserved CD4 cell counts. It rarely affects the orbital region in the setting of AIDS. We report unusual presentation of a fatal case of AIDS-associated BL in a 42-year-old female patient with severe CD4 cell depletion who presented with dramatic fast growing (within days) bilateral orbital masses leading to striking facial deformities. To the best of our knowledge, this is the first report of bilateral orbital involvement in AIDS-associated BL.